Verdad, redundancia y aserción : hacia una visión expresivista de la verdad (2017)
This thesis is about Truth. The approached from which it is addressed is a logico-semantic analysis. What is defended is that such analysis leads to an expressivist view of truth. Truth has an expressive meaning, and this is understood once an analysis of the complex logical and semantic function that it performs within the natural language is made. The text is divided into two parts, each one composed by two chapters. In the first part, titled "the complex function of truth", the logical-semantic analysis of truth is displayed. In this part the text analyzes: (i) what is the relationship between truth terms and other linguistic signs within true ascriptions, (ii) what can be said through a truth ascription, and (iii) what the speakers do when they attribute truth to a proposition. The second part, entitled "towards an expressivist vision of truth", provides the necessary elements to assert that the complex...